Algorithm 759: VLUGR3 a vectorizable adaptive-grid solver for PDEs in 3D?Part II. code description. - Blom, J. G. (ACM transactions on mathematical software.)
This article describes an ANSI Fortran 77 code, VLUGR3, autovectorizable on the Cray Y-MP, that is based on an adaptive-grid finite-difference method to solve time-dependent three-dimensional systems of partial differential equations.